Theoretical Study of the Iron Complexes with Aminoguanidine: Investigating Secondary Antioxidant Activity - Guillermo García-Díez; Nelaine Mora-Diez (MDPI AG, 2020)
A thorough analysis of the thermodynamic stability of various complexes of aminoguanidine (AG) with Fe(III) at a physiological pH is presented. Moreover, the secondary antioxidant activity of AG is studied with respect to its kinetic role in the Fe(III) reduction to Fe(II) when reacting with the superoxide radical anion or ascorbate. Calculations are performed at the M05(SMD)/6-311+G(d,p) level of theory. Solvent effects (water) are taken into account in both geometry optimizations and frequency calculations employing the SMD solvation method. Even though the results of this study show that AG can form an extensive number of stable complexes with Fe(III), none of these can reduce the rate constant of the initial step of the Haber-Weiss cycle when the reducing agent is <semantics><msubsup>O2•−</msubsup></semantics>. However, when the reductant is the ascorbate anion, AG is capable of reducing the rate constant of this reaction significantly, to the point of inhibiting the production of •OH radicals. In fact, the most stable complex of Fe(III) with AG, having a <semantics>∆<msubsup>Gf°</msubsup></semantics> of −37.9 kcal/mol, can reduce the rate constant of this reaction by 7.9 × 105 times. Thus, AG possesses secondary antioxidant activity relative to the Fe(III)/Fe(II) reduction with ascorbate, but not with <semantics><msubsup>O2•−</msubsup></semantics>. Similar results have also been found for AG relative to the Cu(II)/Cu(I) reduction, in agreement with experimental results.